Development of Bio-Based Materials (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
The shift towards a sustainable and circular economy is one of today's most pressing challenges. Growing global demand for materials, along with concerns about environmental impact and resource depletion, has fuelled interest in innovative polymeric materials that support sustainability, recyclability, and advanced functionality. Given the increasing interest in this field, this reprint brings together a selection of 19 innovative research articles originally published in the Special Issue “Development of Bio-Based Materials: Synthesis, Characterization, and Applications II”. These studies highlight recent advances in polymer science, with a strong focus on sustainability, recycling, bio-based materials, biomedical applications, and advanced functional materials. Designed as a valuable resource for researchers, engineers, and professionals in polymer science, materials engineering, and sustainability, this collection aims to inspire further innovation in bio-based materials and their applications.